Impact of Financial Crisis on GDP Growth: The Case of Developed and Emerging Countries - Kouki, Mondher; Belhadj, Rym; Chikhaoui, Monia (International Journal of Economics and Financial Issues, 2018)
The purpose of this paper is to examine the effect of banking, monetary, and twin crises on the economic growth of a sample of 28 emerging and developed countries over the period 1980-2011. By considering a comparative analysis of the impact of the three types of crises, we found that the effect of banking crises is more expensive and deep than monetary crises on GDP growth. As for the twin crisis, with a simultaneous occurrence of a monetary and a banking crisis, the effect seems to be more serious and more persistent than the other types of crises. This negative effect is more pronounced when we take into account variables related to the status of the financial system, liberalization, and the level of institutional development. Keywords: Financial Crisis, Economic Growth, Financial Liberalization, Generalized Method of Moments JEL Classifications: C32, G01, O40